Long-duration energy storage in transmission-constrained variable renewable energy systems - Andrew K. Chu; Ejeong Baik; Sally M. Benson (Cell Reports Sustainability)
Summary: We assess the role of multi-day to seasonal long-duration energy storage (LDES) in a transmission-constrained system that lacks clean firm generation buildout. In this system, unless LDES is extremely inexpensive, short-duration energy storage (SDES) delivers 6–10× more electricity and has a consistently lower levelized cost. LDES substitutes for the role of a dispatchable firm resource. Next, we introduce the concept of a substitution ratio, which quantifies the interchangeability of different generation and storage resources. We show that in this system, 1 MW of LDES has the same system value as 14–19 MW of solar or wind with SDES, emphasizing that LDES is difficult to replace as a dispatchable baseload resource. Unlike other valuation metrics such as levelized cost, substitution ratios can quantify the system-level value of many different resources. Science for society: If emissions-free power from controllable sources such as nuclear energy or fossil fuels with carbon capture and storage is not accessible, long-duration energy storage (LDES) is essential for decarbonizing the electricity grid, as it helps balance supply and demand of electricity over extended periods when solar and wind power are unavailable. Our modeling shows that when LDES is affordable, it can reliably provide steady power, filling a role that is difficult for solar, wind, and other storage technologies to replace. Importantly, our study shows that short-duration energy storage (SDES) from batteries is also very valuable for the grid and that decarbonization is most cost effective when a portfolio of multiple generation and storage options is available. This research offers guidance for policy-makers and industry leaders to accelerate and lower the costs of grid decarbonization.